Seppômen maps for geomorphic developments analysis: the case of Paraná plateau border, Faxinal, State of Paraná, Brazil - doi: 10.4025/actascitechnol.v34i1.9944 - Couto, Edivando Vitor; Fortes, Edison; Sordi, Michael Vinicius; Marques, Américo José; Camolezi, Bruno Aurélio (Acta Scientiarum. Technology, 2011)
Â This article presents the seppômen map technique through the computer application by using the free GIS software SPRINGÂ®. The methodology was applied to the study in the case of the geomorphologhical evolution of the Parana plateaux edges contained in the Faxinal topographic sheet - state of Paraná - Brazil, the results were the digital elevation models (DEM) and topographic shapes that leads to the landform evolution of the area both by differential erosion but also by strong tectonic control.